Erratum: Mahmudul Hasan, Mitsuru Kuramoto, Mohammed Mafizul Islam, Mohammad Shafiqul Alam, Md. Mukhlesur Rahman Khan & Masayuki Sumida (2012) A new species of genus Hoplobatrachus (Anura, Dicroglossidae) from the coastal belt of Bangladesh. Zootaxa, 3312, 45–48. - Hasan, Mahmudul; Kuramoto, Mitsuru; Islam, Mohammed Mafizul; Alam, Mohammad Shafiqul; Khan, Md. Mukhlesur Rahman; Sumida, Masayuki (Zootaxa, 2012)
(Erratum)